Accidental ingestion of foreign object: Systematic review, recommendations and report of a case - Karthik Venkataraghavan; A. Anantharaj; P. Praveen; S. Prathibha Rani; B. Murali Krishnan (Saudi Dental Journal)
One of the serious complications during a routine endodontic procedure is accidental ingestion/aspiration of the endodontic instruments, which can happen when proper isolation is not done. There are at present no clear guidelines whether foreign body ingestion in the gastrointestinal tract should be managed conservatively, endoscopically or surgically. A 5 year old boy reported to the Department of Pediatric and Preventive Dentistry, D.A. Pandu Memorial R.V. Dental College, Bangalore, India, with a complaint of pain and swelling in the lower right back teeth region. Endodontic therapy was planned for the affected tooth. During the course of treatment the child accidentally swallowed a 21 mm 15 size K file. Endoscopy was performed immediately but the instrument could not be retrieved. The instrument passed out uneventfully along with the stools 48 h after ingestion.Careful evaluation of the patient immediately after the accident helps in managing the patient effectively along with following the recommended guidelines. Keywords: Foreign body, Canal, Instrument, Swallowing, Rubber dam, Isolation, K-file, Endoscopy, Accidental ingestion, Endodontic procedure, Dental materials, Aspiration, Caries, Dental care for disabled children, Radiography, Dental prostheses, Dental restoration, Emergencies, Endodontic files, Endodontics, Dental instruments, Foreign bodies